Manual dexterity in patients with Asperger's syndrome: evidence for a selective deficit of predictive motor control - Riegg, F.P; Vogeley, K; Dafotakis, M; Timmann, D; Fink, G.R; Nowak, D.A (Aktuelle Neurologie, 2008)
Background: The cerebellum has been shown to play an important role of predicting the sensory outcomes of one's own movements. Abnormalities of the cerebellum have been consistently reported in Asperger and autistic individuals. Here we investigated predictive and reactive programming of grip and grasping movements in patients with Asperger Syndrome (AS). Methods: 12 right-handed patients with AS and 12 healthy sex- and age-matched control subjects held a receptacle instrumented with grip force and accelerations sensors with the thumb and either fingers in opposition while a load was dropped either expectedly from the subjects opposite hand (predictive condition) or unexpectedly from the experimenter's hand (reactive condition). Subjects performed each experiment both with eyes open and closed. In addition, a reach-to-grasp and lift task was performed in four conditions, which differed in the weight and size of the object to be grasped and lifted. Experiments were performed with both hands. IQ-Score of each subject and Autism Spectrum Quotient (AQ) of Asperger individuals were assessed. Results: Our preliminary results show, that Asperger patients compared to healthy individuals showed mild to moderate impairments of predictive force control in all motor tasks under investigation, whereas reactive force control was unimpaired. Deficits in predictive force control were significantly correlated with the IQ-Score, but not with the Autism Spectrum Quotient. Conclusion: Our data provide kinematic evidence for sub-clinical deficits of predictive motor control in Asperger syndrome. These behavioural findings may reflect cerebellar dysfunction and fit well with structural abnormalities of the cerebellum that have been reported in Asperger subjects. Future research is needed to shade some more light onto these issues.